Pengaruh Kompensasi dan Disiplin Kerja terhadap Produktivitas Kerja melalui Kepuasan Kerja pada PT. Perkebunan Teh Assam Jayanegara Indah Sukabumi - Palahudin, Palahudin; Samsuri, Samsuri; Gea, Fendiaman (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the effect of compensation and work discipline on work productivity through job satisfaction as an intervening variable at PT. Perkebunan Teh Assam Jayanegara Indah Sukabumi. The research method is quantitative with path analysis technique. The sample consists of 100 respondents selected through purposive sampling. The results show that compensation and work discipline significantly influence job satisfaction and work productivity. Furthermore, job satisfaction acts as an intervening variable mediating the relationship between compensation, work discipline, and work productivity. Therefore, effective compensation and work discipline improvements can enhance employee satisfaction and productivity.